2019
DOI: 10.1111/jopr.13016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Occlusal Intercuspal Angulation on the Quality of CAD/CAM Lithium Disilicate Crowns

Abstract: Purpose Modification of intercuspal angulation (ICA) influences the amount of tooth structure removal, which may impact the retention and resistance form of the preparation. This study evaluated the impact of ICA on the marginal gap of CAD/CAM crowns and the influence that tooth structure removal, caused by variation of ICA, has on the resistance and retention form of the preparation. Materials and Methods Sixty ivorine molars were manufactured with various ICAs (100°, 110°, 120°, 140°, 160°, and 180°; 10 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Such a design may reduce milling times, improve accuracy, and expedite the treatment process, all of which will enhance the overall quality of CAD-CAM crowns [9,40]. However, two recent studies have demonstrated that preparing a nonanatomical occlusal surface leads to a significantly larger marginal gap on CAD-CAM crowns [9,41]. Preparing non-anatomical occlusal surface results in more tooth structure loss, a factor that may influence the resistance and retention form of the preparation [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a design may reduce milling times, improve accuracy, and expedite the treatment process, all of which will enhance the overall quality of CAD-CAM crowns [9,40]. However, two recent studies have demonstrated that preparing a nonanatomical occlusal surface leads to a significantly larger marginal gap on CAD-CAM crowns [9,41]. Preparing non-anatomical occlusal surface results in more tooth structure loss, a factor that may influence the resistance and retention form of the preparation [41].…”
Section: Introductionmentioning
confidence: 99%
“…However, two recent studies have demonstrated that preparing a nonanatomical occlusal surface leads to a significantly larger marginal gap on CAD-CAM crowns [9,41]. Preparing non-anatomical occlusal surface results in more tooth structure loss, a factor that may influence the resistance and retention form of the preparation [41].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to conventional complete coverage restorations, the longevity of all‐ceramic crowns is affected by the principles of tooth preparation such as total occlusal convergence (TOC), the occlusocervical/incisocervical dimensions, the presence or absence of undercuts, the amount of occlusal reduction, finish line form and depth, and finish of the preparation 5,6 . When one is preparing a tooth for an all‐ceramic crown using a complete digital workflow that includes recording with an intraoral scanning device (IOS) followed by crown fabrication with CAD/CAM technology, certain principles of tooth preparation such as the quality of the finish line design, line angle form, and design of occlusal surface (anatomical, semi‐anatomical, or non‐anatomical) become essential 7‐9 . In addition to an acceptable tooth preparation, the quality of a CAD/CAM crown is dependent on the optical scanner interface, defining internal settings of the restoration in the design software, the manufacturing process, and the type of material used for fabrication of the restoration 10‐17 …”
mentioning
confidence: 99%
“…Previously, modifications on the anatomical features of the occlusal surface were suggested to compensate for the milling process; as a result, a simple practical occlusal reduction design with a non‐anatomical occlusal surface was recommended as this modification may reduce milling times, improve accuracy, and expedite the treatment process, thereby enhancing the overall quality of CAD/CAM crowns 8,33 . However, two recent studies found that preparing a non‐anatomical occlusal surface led to a significantly larger marginal gap 8,9 . In addition, preparing a non‐anatomical occlusal surface resulted in more tooth structure loss, a factor that may influence the resistance and retention form of the preparation 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation